PKM PENGENALAN PEMBUATAN NUTRISI HIDROPONIK BAGI MAHASISWA PROGRAM STUDI AGRIBISNIS FAKULTAS PERTANIAN UNIVERSITAS KRISTEN PAPUA - Leiwakabessy, Ivonne (SOLIDEO Jurnal Pengabdian Masyarakat, 2025)
This community service activity aimed to enhance students' knowledge and skills in understanding and practicing the preparation of hydroponic nutrient solutions. Students from the Agribusiness Study Program, Faculty of Agriculture, Papua Christian University, were selected as the target participants due to their relevant academic background and potential to be agents of change in the community. The activity's implementation methods included theoretical material on the basic concepts of hydroponic nutrition, practical mixing of AB mix solutions with PPM and pH value measurements, and evaluation through pre-tests and post-tests. The results of the activity showed an increase in students' knowledge and skills in independently mixing nutrient solutions, as well as a growing interest in developing hydroponic practices outside of the training activities. This activity successfully had a positive impact on the students and can be further developed into a hydroponic-based agribusiness entrepreneurship program within the campus environment.